EATING PATTERNS AND NUTRITIONAL STATUS OF CHILDREN'S AGE PRE-SCHOOL IN PUSKESMAS MELONGUANE TALAUD ISLANDS - Adi Yeremia Mamahit; Vera Karame; Misra A. Niomba (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2019)
Background: Nutritional status in children aged 1-5 years is still a major health problem in the world including the country of Indonesia. Indonesia is a developing country that still faces considerable nutritional deficiencies. World Health Organization (WHO) estimates that 54% of causes of death in infants and toddlers are based on poor nutrition. Aims are to determine the relationship between eating patterns with the nutritional status of pre-school age children in the Public Health Center in the Melonguane sub-district. Methods: This research uses correlation analytic research with cross-sectional approach. This research was carried out in the Melonguane Community Health Center, Melonguane District, Talaud Regency. Sample as many as 33 pre-school age children (3-5 years). Based on statistical tests using the Chi-Square test with indigo ρ = 0.007 smaller than the value of α = 0.05, which means the null hypothesis is rejected. Conclusion: Most pre-school age children in the work area of ​​the Melonguane Health Center in the District of Melonguane have a good diet. Most pre-school-aged children in the Melonguane Community Health Center area of ​​Melonguane District have normal nutritional status. There is a relationship between eating patterns with the nutritional status of pre-school-aged children in the working area of ​​the Melonguane Community Health Center, Melonguane District, normal nutritional status.